(untitled) (International Congress on Economics, Management and Business Studies, 2026)
The history of mankind begins with the beginning of the labor process. Labor, in turn, began with the preparation of labor tools. As the place where primitive people began to make such initial labor tools, Central Asia is also recognized as one of the cradles of humanity. This places great tasks on the shoulders of historians and archaeologists. The study of the settlements and labor tools of primitive people living in Central Asia is recognized as one of the most pressing issues facing archaeological science today. Because the study of the types of labor tools and the development of their processing techniques allows us to assess the development of human thought.